The Effects of Self-talk on a Novel Task in Football in Elementary Physical Education Students - Zourbanos, Νίκος; Bardas, Δημήτρης; Hatzigeorgiadis, Αντώνης (Inquiries in Physical Education and Sport, 2012)
The purpose of the present study was to examine the effects of motivational and instructional self-talk on a new kinetic skill in football (shooting with the non-dominant foot) in young elementary physical education students. Participants were 60 pupils (38 boys και 22 girls) aged between 10-12 years (Μ =10.90, S.D = .68). The performance test in this experiment involved shooting from 12 meters distance in modified goalposts (width of 1 meter). For the purposes of the present experiment participants were randomly assigned into two experimental groups (motivational and instructional self-talk) and a control group. The results revealed that instructional self-talk was more effective than motivational self-talk in a new kinetic skill such as shooting with the non-dominant foot during the physical education lesson. Finally, suggestions for the application of the strategy in the school settings are proposed.